Electrical Status Epilepticus During Sleep - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Eighteen children with medically refractory seizures, language deterioration, incoordination, and regression in behavior and intellect, and an EEG showing electrical status epilepticus during sleep (ESES), are reported from Beijing Medical University, and the University of Hong Kong, Republic of China.